HEALTHCARE PRACTITIONERS’ KNOWLEDGE AND AWARENESS ON PERINATAL DEPRESSION IN KUANTAN, PAHANG, MALAYSIA - Hassan, Noor Artika (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to assess the knowledge and awareness of healthcare providers about perinatal depression and the factors associated with it. Methodology: A quantitative cross-sectional study was conducted on Maternal and Child Health (MCH) clinics in Kuantan, Pahang. 220 healthcare practitioners (HCPs) completed the survey, which consisted of 20 items and 13 items for knowledge and awareness, respectively. Results: The participants’ mean knowledge and awareness scores were 9.47 and 44.78, respectively. The results showed low level of knowledge and moderate awareness on perinatal depression (PND) among the HCPs. Medical doctors and single-respondents had a higher mean knowledge score on PND (P<0.05). Most HCPs scored above 60% on symptom-related questions and postpartum depression management.Only 32.7% and 16.4% of them scored the questions related to risk factors and treatment for antenatal depression. Recommendation: Continuing professional education is necessary in order to improve the levels of comprehension of PND among HCPs in the Kuantan.